THE FESTIVALS OF THE ALPINE - KALITA ETHNIC GROUP (CAHIERS MAGELLANES-NS, 2024)
Various ethnic and racial groups have long contributed various components to the Assamese people's overall cultural mosaic, the micro-nationalistic groups that were crucial in the development of Aryan culture created the fundamental foundation of this. Originally, they were known as "Kambojas," who came from a border region in South-East Iran and later settled in Assam's lush river valley regions. It appears that no other human race visited or lived in Assam prior to the Alpines. There are no documentary references to support the claims made about the groups that inhabit the state's hilly areas. come to Assam before those who came from the borders of the South–East Iran. From the mode of their attires, food – culture and habit, animal husbandry, weaponry and war-tactics, the Astro–Asiatic and the Mangoloids show their own identifiable features, that are to the fact that they have been settling over the hills and the high lands of the region since their entry into this land, instead of choosing the plains and river valleys for this. The lack of historical records makes it difficult to confirm the claims of the groups inhabiting Assam's hilly areas  It is interesting to note that they preferred settling in the hills and highlands rather than the more accessible plains and river valleys, pointing to a deliberate choice in their migration patterns.  Geographical features, security concerns, and cultural traditions are just a few of the variables that might have affected this choice.As a populous caste of Assam, the Kalitas have immense contributions to make into the Assamese folk cultural landscape.According to Kali Ram Medhi: “Assam is the homeland of the Kalitas, and its civilization is predominantly Kalita. The other sub-castes follow the Kalita social laws and customs in their entirety”. In its process of contributing to the formation of the greater Assamese race, the Kalitas had its own share of ethnic customs, conventions, and various other folk elements, and in that way, it has also allowed itself to consecrate many of its own original features or elements. In this article, we will discuss the festivals of Kalita's, how they are celebrated with great enthusiasm, and traditional rituals.